The Insider Voice about Prostitution. Issue 1 (June 2017) - Sahu, Arti; Mondol, Reshma; Khatoon, Fatima; Chettry, Neelam; Khatoon, Nageena
This piece* has been put together by drawing from Red Light Despatch (RLD), a monthly newsletter brought out by Indian anti-sex trafficking organization Apne Aap Women Worldwide. RLD is for the women of the red-light area by the women of the red-light area. Women, girls and men trapped in prostitution from the red-light areas of Bihar, Delhi, Maharashtra, Rajasthan, and West Bengal write the Despatch. They write for each other and share information, dreams, struggles and hopes in solidarity from different corners of India. They try to address the gaps in mainstream media that often do not cover information that is relevant to the poor and the marginalized. RLD also serves as a mouthpiece for prostituted women and survivors to end sex trafficking. The narratives in RLD reveal that prostitution is a form of violence against women and the only way to end it is by internalizing the Gandhian principles of ahimsa (non-violence) and antyodaya (uplift of the last). The narratives speak of how the prostituted child and woman is always originally trafficked and that she is the victim of structural violence as a female, as a person from the countryside, as a person from a scheduled caste/scheduled tribe or other backward classes and of unequal and lopsided development; and how difficult it is to exit prostitution.